Comparative Study and Preservation of Marriage Traditions: Samawa Ethnicity and Mbojo Ethnicity, West Nusa Tenggara - Ilmiawan, Ilmiawan; Sarah, Fidlia Mae (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This article aims to analyze the differences that exist in the pre-marriage tradition (malam tempel pacar or pancar) of the Samawa Tribe and the Mbojo Tribe on the island of Sumbawa, Indonesia.  The research method used in this article is historical research and uses a qualitative approach. The stages in historical research, namely heuristics, verification, interpretation, and historiography. The results of the study found that the pre-marriage tradition (tempel pacar or pancar) of the Samawa Tribe and the Mbojo Tribe in addition to having similarities also has significant differences. The difference lies in the philosophy and implementation process. The Samawa tribe believes that this tradition is a form of purification of the body and soul of the bride and groom before marriage. While the Mbojo Tribe carried out this tradition because it became an example for women who were going to marry classes and became a forum for the spread of Islam during the royal era. The difference in the implementation process that is clearly visible is the accompaniment used. The Samawa tribe uses Gong Genang while the Mbojo tribe is accompanied by dhikr and chanting solawat or known as Ziki Kapanca. This tradition still exists in both tribes and is still carried out today.